Application Planning of Microhydro Electricity Generating Technology With 55 Kw Power in The Mountains Using The River Flow of Coban Rondo Waterfall, Krajaan, Pandesari, subdistrict Pujon, Malang, East Jawa - Lazuardi Lazuardi; Muhammad Akhlis Rizza; Maryono Maryono (Journal of Evrímata: Engineering and Physics, 2023)
Abstract, In industry 5.0 availability of electricity plays an important role in the economic development of the community. In the villages on the slopes of the mountain there are still some villages that have not been connected to electricity so that the economic activity of the community is disrupted. Micro hydro electricity generation technology can be a solution to overcome the problem of the need for electrical energy in villages around the mountain slopes by utilizing differences in the height of the area and the flow rate of water from the river which has the potential to act as a turbine generator to be used as electricity to flow into the community to support community economic activities around the mountain slope. along with the existence of energy containers, the economy of the people on the slopes of the mountain will develop.